The Influence of the Culturally Responsive Teaching Approach on Learning Observation Results Report Text Writing Skills - Clara Naida Wardani; Trinil Dwi Turistiani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The Culturally Responsive Teaching (CRT) approach is a learning approach that is believed to optimize learning outcomes. The CRT approach is believed to improve the skills of writing observational report texts (LHO). This study aims to describe: 1) the implementation of learning using the CRT approach for LHO text writing skills. The study used a quasi-experimental quantitative approach with a nonequivalent control group design. The research sample was selected using a simple random sampling technique, finding the experimental class (VIII C) and the control class (VIII D). Learning data were collected using a non-test instrument, namely observation guidelines. Learning outcome data were analyzed using parametric inferential statistical procedures assisted by SPSS version 25. The results of the study showed that the implementation of learning went very well, evidenced by the observation score of educator activity of 89% and student activity of 90%; 2) learning outcomes in the experimental class were 29 students (90.63%) who completed learning with a score of 80.00, while in the control class only 20 students (62.50%). The mean value of the initial test of the experimental class was 52.81 which increased by 85.94. Meanwhile, the mean value of the initial test of the control class was 52.66 which increased to 76.72. Changes in learning outcomes in the experimental class were higher than those in the control class. The normality test showed that the data were normally distributed, while the independent t-test produced a Sig. (2-tailed) value of 0.001 < 0.05. Thus, there was a significant influence on the implementation of the CRT approach.